Ethno Botanical Study of Some Misidentified Medicinal Plant Species in Sri Lanka. - Gunasinghe, K.S.L.U.K.; Eriyagama, A.M.U. (University of Jaffna, 2022)
The use of herbal medicine for treating humans' disease has been done since ancient times in Sri Lanka. Indigenous medicine and Ayurveda medicine also origins based on medicinal plants. Therefore, accurate identification of medicinal plants is playing a major role in traditional medicine. However, there are several herbal medicinal plant species with the same botanical names and different plant species called as same scientific names in Sri Lanka. Misidentification of plant species, inadvertent use of totally unrelated species, or by closely related inferior quality species can hinder their medicinal use, the adverse effects of which may even treat to the patients. The objec¬tive of this study is to separately identify and discuss different usages of herbal plant species with the same Sinhala names in traditional medicine. Here, investigated Ten plant species that are commonly used by traditional physicians of Sri Lanka. All the information was collected by a conversation with Ayurveda doctors and traditional physicians. Previous research details and findings were collected from online botanical and Ayurveda journals and also social media. The study was to identify the Ten most used herbal plant species in Sri Lankan traditional medicine. Such as Tinospora cordi¬folia (Rasakida), Hoya ovalifolia (Gonika), Rauvolfia serpentina (Ekaveriya) , Crinum zeylanicum (Goda manel), Baliospermum montanum ( Daththa ) , Cynodon dactylon (Ethana), Hellenia speciose (Thebu), Dregea volubilis (Kiri aguna) , Allamanda ca-thartica (wal ruk aththana), and Indigofera tinctoria (Nil awariya). However, observa-tions confirmed that there were four species of Goda manel, three species of Thebu ,Daththa, Ethana and Nil awariya, two species of Kiri aguna and Wal rukath-thana. The study shows different plants identified as under one name and different plant species contain one scientific name. Further experiments and laboratory analysis for identifying the chemical compositions of every species are needed to predict the exact medicinal value of these plants.
Keywords: Medicinal plant; Misidentification; Ayurveda; Traditional medicine